FORENSIC, SERVICE AND COMBAT SUPPORT OF COUNTERING TERRORIST AND DIVERSION THREATS AT CRITICAL FACILITIES OF INFRASTRUCTURE - Komisarov, Oleksandr; Batiuk, Oleg; Pavlov, Serhii (Honor and Law, 2022)
The authors conduct a study of the provisions of forensic, service and combat support of countering terrorist and diversion threats at critical facilities of infrastructure in the provisions of scientific article. Forensic, service and combat support of countering terrorist and diversion threats at critical facilities of infrastructure have several levels. All these levels of activity are extremely complex and specific in their content, tasks that should be solved, methods and means that should be implemented at the same time. They are characterized by a hierarchical management system, due to the multilevel system of organization of relevant services, units of law enforcement agencies, military forces of law and order and emergency services. Authors consider that forensic, service and combat support of countering terrorist and diversion threats at critical facilities of infrastructure is aimed at forming the conditions that are necessary for creating an optimal structure of activity on combating the relevant crimes, its stages, individual actions of the perpetrators. In conclusion, the authors determine that all levels of forensic, service and combat support of countering terrorist and diversion threats at critical facilities of infrastructure in the presence of fundamental differences in the subject of their activity and the peculiarities of their internal and external interaction have the dual purpose: it is the formation of legal, organizational, scientific, technical, personnel and other conditions of constant readiness of law enforcement agencies to take action to detect and investigate crimes using forensic methods, tools and recommendations; practical-activity one, which is expressed in the professionally competent, tactically verified implementation of such conditions in the daily practice of detection and investigation of crimes.